건물의 냉, 난방 부하비율과 HVAC&R 시스템 1차 에너지 소비량의 상관관계분석 및 합리적 설계방안 연구 - 조진균(Jinkyun Cho); 김진호(Jinho Kim); 이성재(Suengjae Lee); 강호석(Hosuk Kang) (설비공학 논문집, 27(3), 2015)
HVAC&R systems account for more than 50% of the energy consumption of buildings. The purpose of this study is to propose an optimal design method for the HVAC&R system and to examine the possibility for the energy conservation of a selected system. The energy demand for cooling and heating is determined by using TRNSYS and HEET. By an interaction between total system efficiency and cooling-to-heating load ratio, the optimal HVAC&R systems will be decided. The results showed that this proposed method is significantly capable of determining optimal system and building design for saving energy.